Pest Control System on Agricultural Land using IoT Electronic Controller - Ratnasari Nur Rohmah; Yana Oktafianto; Nurokhim Nurokhim; Heru Supriyono; Agus Supardi (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This research aims to assist farmers in controlling plant pests, birds and insect, by applying an appropriate electronic technology. The system operates in an automatic and remote-controlled modes using IoT technology.  We used a solar powered systems that are environmentally friendly with zero carbon emissions, as an energy source for the systems. The test results showed that the bird pest control system worked well according to the automatic and remote-control modes design. We compare those two methods to evaluate the most effective between those two methods. Bird pest control using two actuators, sound and movement, outsmart control using only sound by success ratio 70:50. The insect pest control system worked well with the remote-control mode through Telegram application on farmers’ smartphones.